Gender ideology, family communication, and mother-worker relationships with children - Arindra, Fairuza (Faculty of Communications Science, Dr. Soetomo University, 2025)
The quality of the mother-child relationship is shaped by perceptions of closeness and satisfaction in family life. In recent times, many working mothers have faced challenges in maintaining effective family communication patterns, often leading to gender ideology disagreements about maternal roles and hindering relational quality. This study examines (1) the influence of family communication patterns on the relational quality of working mothers and children, (2) the impact of family communication patterns on gender ideology, and (3) the mediating role of gender ideology in shaping mother and child relational quality. Using a quantitative approach, survey data were collected from 157 working mothers through purposive sampling. Key measures included the Family Communication Patterns Instrument (FCPI) and the Gender Ideology Scale (GIS), analysed using Structural Equation Modelling (SEM). Results indicate that only conversational family communication patterns, mediated by gender ideology, significantly influence mother-child relational quality. These findings highlight the critical role of gender ideology in fostering positive mother-child relationships and suggest the need for family communication strategies that address gender role expectations to support working mothers.